The Role of Planning and Communication the President of The Municipal Authority to Prepare for Installation of Representative Bodies of Local Power (Study of Case in the Municipality of Liquica) - Silva, Adolfo Natalia da; Leonito M. Martins; Mateus X. da Costa Cabral (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objectives of this research in scientific work are several important proposals as follows: Find out the role of the President of the Municipality of Liquica, Analysis to find out the role of the President of the Municipality of Liquica in planning and communication aspects and finally find a hypothesis solution or suggestions to match if there are challenges that paralyze the role of the President of the Municipal Authority of Liquica. The Research Method used is in this research methodology the writer uses qualitative research method. In qualitative research, the presence of researchers as tools as well as data. The presence of the researcher is very necessary, because in addition the presence of the researcher as a data. Primary data and Secondary data interview, documentation at the research site. The results of the research analysis show that the municipality of Liquica is small masker but the relevant authorities and entities are ready to receive the local power facilities that have been planned by the Central Government for a long time to implement. For the reason that this government policy has benefits and it is important that power should not be centralized only in the Central Government with a heavy and longer bureaucracy to hinder the services of the people on the basis and increase an integrated national development process to ensure the well-being of the people and the progress of the country